Outside Directors on Corporate Boards: Background and Behavior - Jaehoon Kim; Hwaryung Lee (Korea Development Institute (KDI), 2015)
The substantial influence of CEOs diminishes the oversight function of the board of directors. Many outside directors have social ties with CEOs and their behavioral patterns are inconsistent with those of vigilant monitors. Dissents are rare, and those who do dissent are highly likely to be replaced. Further, the director ratio tends to be lower when more supervisory items are on the board agenda. In order for the outside director system to operate properly, the voting rights of minority shareholders should be respected, outside directors and agenda selection must remain independent from CEOs, and objective evaluation and disclosure of outside directors' board activities must ensue. - Analysis on corporate data shows that, under the current outside director system, CEOs can immobilize oversight by outside directors. - There is a low possibility of dissent on boards that lack independence from management. - The attendance pattern of friendly outside directors is consistent with delegating decision making to inside directors. - Outside directors rarely cast a dissenting vote, but once they do, they face a higher risk of being replaced. - Outside directors with the same regional or high school background as the CEO face lower replacement risks than those without such connections. - It seems that practical influence of outside directors on boards is low during times when their supervisory role is critical. The situation also implies that CEOs have of the windows of opportunity to obtain approval on sensitive issues at board meetings. - In order to restrict CEOs from intervening in the process of outside director recommendation, it is necessary to strengthen the role of outside directors in the composition of the candidate recommendation committee and to mandate the committee to recommend more than one candidate. - The general shareholders' meeting should be provided with information on objective indices regarding how the board of directors has operated on essential issues. - The CEO should not be allowed to hold the position of board chairman.
Keywords: 330